Moral Elevation and Economic Games: The Moderating Role of Personality - Pohling, Rico; Diessner, Rhett; Stacy, Shawnee; Woodward, Destiny; Strobel, Anja (Frontiers in Psychology, 2019)
Moral elevation is the prototypical emotional response when witnessing virtuous deeds of others. It is a self-transcendent, positive emotion entailing a feeling of warmth in the chest, feeling uplifted and inspired, and motivated to show prosocial or moral behavior oneself. Yet, little is known about the role of individual differences that moderate the susceptibility to experiencing this emotion. The present experiment investigated the role of personality traits as moderators of moral elevation and its behavioral effects using the framework of economic games as a measure for prosocial behavior. One aim was to replicate prior findings on the trait Engagement with Moral Beauty (trait elevation) as moderator for experimentally induced state elevation. A second aim was to explore new potential moderators that were found to be connected to the moral realm: Honesty-Humility, Agreeableness vs. Anger, and Need for Cognition. Third, the present study not only investigated conditions for the state of elevation but also for its behavioral effects, that is, prosocial behavior. A sample of U.S. American college students (N = 144) was randomly assigned to either watch a morally uplifting or a humorous video clip. Afterwards, all participants played a dictator game and an ultimatum game, and were asked to volunteer in another time-consuming experiment. In line with our hypotheses, experimentally induced state elevation promoted prosocial behavior, especially within the dictator game. Also in line with our hypotheses, higher levels of Need for Cognition and higher levels of Engagement with Moral Beauty (but not higher levels of Honesty-Humility and Agreeableness) were a condition to show higher levels of prosocial behavior within the experimental group. However, this was restricted to active cooperation (dictator game behavior). In contrast to our hypotheses, none of our targeted personality traits moderated the proneness to experience the state of elevation but only its behavioral consequences. Our results replicate and extend prior findings on moderators for elevation and exemplify the importance to investigate the role of personality traits in the context of the moral elevation phenomenon.